2014
DOI: 10.4049/jimmunol.1400640
|View full text |Cite
|
Sign up to set email alerts
|

Idiotype-Specific Th Cells Support Oligoclonal Expansion of Anti-dsDNA B Cells in Mice with Lupus

Abstract: Systemic lupus erythematosus (SLE) is marked by a Th cell–dependent B cell hyperresponsiveness, with frequent germinal center reactions and hypergammaglobulinemia. The specificity of Th cells in lupus remains unclear, but B cell Ids have been suggested. A hallmark is the presence of anti-dsDNA, mutated IgG autoantibodies with a preponderance of arginines in CDR3 of the Ig variable H chain (IgVH). B cells can present V region–derived Id peptides on their MHC class II molecules to Id-specific Th cells. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
0
17
1
Order By: Relevance
“…We have previously described IgVH sequences from lupus prone mice suffering from Id-driven lupus ( 33 ). Utilizing a data set of 176 sequences with average of 11 IgVH CDR3 aa (Figure 1 A), we compared CDR3 sequences with microbial sequences utilizing Blastp (microbial sequences include non-redundant data from prokaryotic genome sequencing projects, but not viruses or eukaryotic pathogens such as protozoa and fungi), see Materials and Methods .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously described IgVH sequences from lupus prone mice suffering from Id-driven lupus ( 33 ). Utilizing a data set of 176 sequences with average of 11 IgVH CDR3 aa (Figure 1 A), we compared CDR3 sequences with microbial sequences utilizing Blastp (microbial sequences include non-redundant data from prokaryotic genome sequencing projects, but not viruses or eukaryotic pathogens such as protozoa and fungi), see Materials and Methods .…”
Section: Resultsmentioning
confidence: 99%
“…Another candidate for Th cell antigen is variable regions of antibody, i.e., V region idiotypes, Id. Th cells can have Id:MHC-specific TCR ( 15 33 ). It has been demonstrated that anti-dsDNA B cells can present Id:MHC class II to Id-specific Th cells, undergo the germinal center reaction, differentiate, secrete autoantibodies, and cause vasculitis and nephritis ( 28 , 30 , 31 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, double transgenic mice were created in which the B cells expressed a specific lambda 2 light chain and the T cells expressed a cognate T-cell receptor. These idiotypespecific T cells were found to drive oligoclonal expansion of autoreactive B cells and within a few weeks many of the B cells produced antibodies specific for anti-ds DNA and hypergammaglobulinemia (Aas-Hanssen et al 2014).…”
Section: Mechanisms Of Hypergammaglobulinemiamentioning
confidence: 99%
“…Further proof-of-concept studies using cloned B and T cells from the CSF allowed us to demonstrate that MS patients have T cells specific for antigenic determinants within the variable regions of the immunoglobulins (idiotopes), and that these proliferate, secrete cytokines and kill oligodendrocytes upon antigen stimulation (15)(16)(17)(18). Such mechanisms may allow B cells of various specificities to receive help from T cells specific for an unlinked antigen, an idiotope, and has been shown in mouse models to induce immunoglobulin class switching and cause production of auto-antibodies triggering auto-immune disease (12,19,20). An analogous immune response is the generation of anti-drug antibodies to therapeutic monoclonal antibodies (mAbs), where T cell epitopes were mapped to the variable regions (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%